Dysphagia after stroke - D. O. Gromova; V. V. Zakharov (Неврология, нейропсихиатрия, психосоматика)
The incidence of dysphagia after stroke accounts for 20 to 64%, which makes swallowing disorder one of the most common sequels of acute cerebrovascular accident. Dysphagia may cause life-threatening complications, such as aspiration pneumonia, cachexia, and dehydration. The paper gives international algorithms for the clinical and instrumental evaluation of swallowing function and the diagnosis of aspiration. It sets forth basic principles for managing patients with dysphagia, as well as dietary recommendations for these patients. The authors show the advantages of fast-dissolving oral medicines used in the therapy of patients with dysphagia after stroke. The currently available experience of drug and non-drug treatments for dysphagia in patients after stroke is analyzed.